On the effect of β phase on the microstructure and mechanical properties of friction stir welded commercial brass alloys - Akbar Heidarzadeh; Tohid Saeid (Data in Brief, 2015)
Conventional fusion welding of brass (Cu–Zn) alloys has some difficulties such as evaporation of Zn, toxic behavior of Zn vapor, solidification cracking, distortion, and oxidation [1–3]. Fortunately, friction stir welding (FSW) has been proved to be a good candidate for joining the brass alloys, which can overcome the fusion welding short comes [4–7]. The data presented here relates to FSW of the single and double phase brass alloys. The data is the microstructure and mechanical properties of the base metals and joints.